2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907062
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic dexterity: In-hand manipulation with external forces

Abstract: Abstract-"In-hand manipulation" is the ability to reposition an object in the hand, for example when adjusting the grasp of a hammer before hammering a nail. The common approach to in-hand manipulation with robotic hands, known as dexterous manipulation [1], is to hold an object within the fingertips of the hand and wiggle the fingers, or walk them along the object's surface. Dexterous manipulation, however, is just one of the many techniques available to the robot. The robot can also roll the object in the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
109
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(117 citation statements)
references
References 46 publications
0
109
0
Order By: Relevance
“…We show that assuming feasibility of regrasps we can simplify the CSP solutions of manipulation plans significantly. Structures similar to the grasp-placement space [5] or the grasp-graph [6] can be precomputed to satisfy our regrasp feasibility assumption. Our algorithm takes as input a sequence of relative poses of assembly parts.…”
Section: A Related Workmentioning
confidence: 99%
“…We show that assuming feasibility of regrasps we can simplify the CSP solutions of manipulation plans significantly. Structures similar to the grasp-placement space [5] or the grasp-graph [6] can be precomputed to satisfy our regrasp feasibility assumption. Our algorithm takes as input a sequence of relative poses of assembly parts.…”
Section: A Related Workmentioning
confidence: 99%
“…Contact with the environment can potentially extend the manipulation capability of robotic hands. Recent studies of motion planning based on this concept are [32]- [35], where motion planning is presented in more detail. Note that motion planning is beyond the scope of this study.…”
Section: A Related Workmentioning
confidence: 99%
“…Dafle et al presented a strong case for the benefits of extrinsic dexterity for in-hand manipulation [3]. Even though the robot used in the study is equipped with a rather simple gripper, the authors demonstrated that it is still physically possible to reposition the object in the hand of the robot by taking advantage of resources external to the robot's hand such as gravity, use of external objects for support and inertial forces due to the manipulator's acceleration.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast with [3], our work focuses on one specific manipulation scenario but instead of using discrete preprogrammed actions we design a continuous closed loop control law to move the tool to the target position.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation